The Correlation between Spiritual Needs Fulfillment and Depression Levels among Members of the Coram Deo Christian Community in Malang - Setiawan, Yohanes; Lase, Iman Karyani (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2024)
This study aims to explore the relationship between the fulfillment of spiritual needs and depression levels among members of the Coram Deo Christian community in Malang. A quantitative research design with a survey methodology was employed, involving 30 community members. The results reveal a significant negative correlation between the fulfillment of spiritual needs and depression levels, with a correlation coefficient of ? = -0.510 (p = 0.004). These findings suggest that higher levels of spiritual fulfillment are associated with lower levels of depression, indicating that spirituality may act as a protective factor against depression. Consequently, integrating the fulfillment of spiritual needs and community support within a holistic approach may serve as an effective strategy for the prevention and management of depression, particularly within migrant student communities.